Understanding and perception of RHB Islamic bank’s staff on Islamic banking product / Nur Syazwani Abdul Manan - Abdul Manan, Nur Syazwani (2014)
Islamic banking product is one of banking product that provide to the customer either muslim or non-muslim. For person that not aware about the modus operandi of each product they will see that Islamic banking product just the same like other conventional banking product. Islamic banking product represents an assertion of Religious law in banking transaction where the transaction should be free from the activities prohibited by Islam, as well as free from such element of riba (interest), gambling and ambiguity. Currently there are a lot of issues that arise on the Islamic banking product especially regarding to the issues of halal and haram in transaction such as interest that arise in loan when the customer apply it at the bank. Other than that for the staffs that working at banking industry they are also confuse either their salary from what they have done are from halal source or not. The main purpose of the study is to determine the awareness and perception of Islamic banking worker to their product compare to conventional banking product. There is a lot of article and journal about the understanding and perception of customer either Muslim or non- Muslim towards Islamic banking product but there are only a few research that conduct by researcher about understanding and perception among employee of Islamic banking itself. This is why the study is conducted to see level of understanding and perception among the employee of Islamic banking.